2003
DOI: 10.1152/ajprenal.00408.2002
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-mediated alterations of renal proximal tubular epithelial cell phenotype

Abstract: The aim of this study was to characterize the mechanism of transforming growth factor (TGF)-β1-mediated alteration of renal proximal tubular cell phenotype. TGF-β1 altered cell phenotype, with cells appearing elongated and spindle shaped. This was associated with loss of cell-cell contact and rearrangement of the actin cytoskeleton, increased formation of stress fibers, and focal adhesions. Addition of the tyrosine phosphatase inhibitor sodium orthovanadate also led to rapid but transient loss of cell-cell con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 37 publications
10
78
1
Order By: Relevance
“…TGF-β1 decreases connexin-43 production Following in vitro activation of latent TGF-β1 by repeated freeze-thaw cycles in 7 day conditioned medium [34], a subsequent 48 h exposure of cells to the activated medium significantly decreased connexin-43 levels to 72±2.1% (mean±SEM) of that with conditioned 5 mmol/l control medium (n03; p<0.05) (Fig. 5a).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…TGF-β1 decreases connexin-43 production Following in vitro activation of latent TGF-β1 by repeated freeze-thaw cycles in 7 day conditioned medium [34], a subsequent 48 h exposure of cells to the activated medium significantly decreased connexin-43 levels to 72±2.1% (mean±SEM) of that with conditioned 5 mmol/l control medium (n03; p<0.05) (Fig. 5a).…”
Section: Resultsmentioning
confidence: 94%
“…f Neutralisation of E-cadherin ligation using an immunoneutralising antibody (20 μg/ml) also restricted intercellular communication and prevented dye transfer. Scale bar 50 μm any suggested cellular migration associated with EMT [34,35]. The cadherin-catenin complex is crucial in epithelial cell-to-cell adhesion and facilitates cell communication via GJs.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we demonstrated the existence in gastric adenocarcinoma AGS cells of a complex composed of Smad proteins, TCF4, and ␤-catenin. Several published studies have recently reported on interactions between Wnt and TGF-␤ signaling (21,22,25,47,48). The TCF/LEF members have emerged as the integral players in coordinating Wnt and TGF-␤ signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of TGF-β, both E-cadherin and β-catenin undergo degradation, with the resulting loss of intercellular junctions. At the same time, cytoplasmic accessibility of β-catenin becomes augmented and its transport to the cell nucleus becomes possible [58].…”
Section: Disturbances In Cadherin/catenin Complex and Epithelial-mesementioning
confidence: 99%